2018
DOI: 10.3390/ijms19123786
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin and Its Metabolites Ameliorate UVR-Induced Mitochondrial Oxidative Stress in Human MNT-1 Melanoma Cells

Abstract: Melatonin (Mel) is the major biologically active molecule secreted by the pineal gland. Mel and its metabolites, 6-hydroxymelatonin (6(OH)Mel) and 5-methoxytryptamine (5-MT), possess a variety of functions, including the scavenging of free radicals and the induction of protective or reparative mechanisms in the cell. Their amphiphilic character allows them to cross cellular membranes and reach subcellular organelles, including the mitochondria. Herein, the action of Mel, 6(OH)Mel, and 5-MT in human MNT-1 melan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 89 publications
4
43
0
Order By: Relevance
“…It neutralizes pigmentation disturbances mediated by exogenously applied melanogenic inhibitors. The molecular mode of action of melatonin may be related to the fact that it tends to maintain cellular homeostasis as observed earlier when it attenuates oxidative stress,, apoptosis and inflammation in normal cells while stimulating it in cancer cells. Herein, melatonin's action on pigmentation opens new regulatory targets for this molecule.…”
Section: Resultsmentioning
confidence: 96%
“…It neutralizes pigmentation disturbances mediated by exogenously applied melanogenic inhibitors. The molecular mode of action of melatonin may be related to the fact that it tends to maintain cellular homeostasis as observed earlier when it attenuates oxidative stress,, apoptosis and inflammation in normal cells while stimulating it in cancer cells. Herein, melatonin's action on pigmentation opens new regulatory targets for this molecule.…”
Section: Resultsmentioning
confidence: 96%
“…Normal neonatal human melanocytes (Cell Applications, Inc) were cultured in melanocyte medium (Medium254) supplemented with human melanocyte growth supplement (HMGS) (Thermo Fisher Scientific). MNT‐1 cells were maintained in DMEM supplemented with 20% ( v / v ) heat‐inactivated fetal bovine serum, 2 mM L‐glutamine, 10 mM HEPES, 1 mM sodium pyruvate, 1% ( v / v ) NEAA, and 1% ( v / v ) streptomycin‐penicillin solution at 37°C in a humidified atmosphere of 5% CO 2 in air . Cells in the logarithmic growth phase were used in all experiments, while 80%‐90% monolayers of confluent MNT‐1 cells were harvested with a mixture of 0.05% trypsin‐EDTA solution.…”
Section: Methodsmentioning
confidence: 99%
“…Melatonin is a naturally occurring molecule assumed to be present in every species [ 19 ]. Due to its antioxidant, anti-inflammatory, as well as other properties [ 20 , 21 , 22 , 23 , 24 , 25 ], it has been speculated to be a promising molecule for treating COVID-19 patients [ 18 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ], and also other deadly viral infectious diseases [ 48 , 49 , 50 , 51 ]. A small scale clinical trial has also shown promising results [ 52 ].…”
Section: Introductionmentioning
confidence: 99%